Increased Technology Provision and Learning: Giving More for Nothing? - Quillérou, Emmanuelle (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
The development of new communication technologies has led to a push for greater technology use for teaching and learning. This is most true for distance learning education, which relies heavily on new technologies. Distance learning students, however, seem to have very limited time available for studying and learning because of work and/or family commitments. This paper focuses on the actual use by distance learning students of different teaching and learning resources and their associated teaching technologies (learning tools). The organisation of one module has been conceptualised as a toolbox, encompassing all the learning tools provided to students. This toolbox also explicitly includes an embedded priority system for the examination of available learning resources, conceptualised as a traffic-light toolbox in this paper. Results from a survey on the resources actually used by students show that students are indeed time-constrained. Students consequently follow the priority system embedded into the module and do not use non-examinable resources much. This paper concludes that students’ specific needs or situations need to be considered for the design of an effective learning toolbox, as opposed to just providing a bundle of learning tools that may be effective on their own.